How strong is the evidence for using blood biomarkers alone to screen for alcohol consumption during pregnancy? A systematic review. (June 2017) - Howlett, Helen; Abernethy, Sarah; Brown, Nigel W.; Rankin, Judith; Gray, William K.
Abstract: Accurate and early identification of women at risk from alcohol consumption during pregnancy allows education and support programmes to be targeted at those most in need. We aimed to conduct a systematic review to compare the efficacy of blood analysis and maternal self-report in detecting at risk women during pregnancy. This review investigated diagnostic accuracy. We searched four databases (Medline, Embase, Psychinfo and CINAHL) for relevant articles and conducted hand searches of recent issues of key journals in the field. No restriction was placed on inclusion in terms of publication date or language. Studies were deemed eligible if they were original research and included a direct comparison of the results of blood biomarker analysis and self-reported alcohol use for the detection of alcohol consumption in pregnant women. Quality appraisal of included studies was conducted using the QUADAS II tool. Eight studies met the inclusion criteria. Gamma-glutamyltransferase (GGT) was investigated in five studies, mean corpuscular volume (MCV) and phosphatidylethanol (PEth) in three studies and carbohydrate deficient transferrin (CDT), aspartate aminotransferase (AST), alanine aminotransferase (ALT) and whole blood associated acetaldehyde assay (WBAA) were each investigated in two studies. Although all of the studies were rated of good methodological quality, none of the biomarkers had both high sensitivity and specificity when compared to self-report. There was some evidence that a combination of biomarkers, or combining biomarkers with self-report, increases accuracy. In summary, the blood biomarkers examined were of limited use in screening for low and moderate alcohol consumption in pregnancy when compared to self-report. However, certain biomarkers, such and CDT and PEth may complement self-report and help improve the accuracy of diagnosis.